Immediate effects of dynamic lycra® orthosis on sitting to standing ability children with cerebral palsy / Ida Hasni Shaari - Ida Hasni , Shaari (2020)
Children with Cerebral Palsy (CP) are highly exposed to postural mal-alignment which interrupt their functional movement pattern and the ability to attain certain functional activities, like walking and Children with Cerebral Palsy (CP) are highly exposed to postural mal-alignment which interrupt their functional movement pattern and the ability to attain certain functional activities, like walking and sitting-to-standing motion (STS). Orthoses are commonly prescribed to give good posture in these children. Yet, none of the orthoses has been found to be suitable in addressing trunkpelvis alignment in children with cerebral palsy, to enhance their STS performance. Therefore, this study was conducted to explore the interface pressure profile and evaluate the effects of newly constructed Dynamic Lycra® Orthosis (DLO) on trunk and pelvis range during STS, in children with CP. A total of 20 Typically-developed (TD) children and 12 children with CP was recruited for this study. Three-dimensional (3D) motion analysis was used to determine the baseline of trunk and pelvis range, during STS in TD and CP group. Each child was seated on a backless and armless chair barefoot. The children performed STS motion at a self-selected speed, for children with CP, they performed the STS motion with an assistance from a walking frame. The second of 3D motion analysis was captured for CP group when the child was wearing the DLO. The differences between the STS movement with- and without DLO were analysed using Wilcoxon signed rank test. Effects size analysis was conducted using Cohen’s d formula to evaluate the effects of DLO on trunk and pelvis ranges. A separate analysis was conducted to compare to effects of DLO with other orthoses; at the same time investigating the interface pressure exerted by the orthosis over trunk and pelvis during STS. There are significant differences on CP child’s trunk and pelvis range during STS, when wearing the DLO and other orthoses (p < 0.05). Effects size analysis indicate that DLO provide between small (< 0.02) to extremely large (> 1.3) effects size pelvic range immediately after application. After 1-week application, the effects size only remain on child CP3 and CP7, for trunk and pelvic movement in sagittal plane. The DLO interface pressure is found to be significantly different in sitting, during STS and in standing position (p< 0.05). The DLO exerted higher interface pressure over trunk segment (mean±SD = 122±1.5 mmHg) compared to pelvic-thigh segment (mean±SD=120±1.8 mmHg). Overall, DLO produce significant different on the trunk and pelvic range during STS in children with CP. The effects however were found to remain only in two of the children with CP, for trunk and pelvic movement over sagittal plane. Next, the DLO interface pressure is found not uniform and graded, significantly different at different posture.